THE ASSOCIATION OF FOOD INSECURITY WITH DIET QUALITY AND MENTAL HEALTH AMONG IIUM KUANTAN STUDENTS - NOR AHMAD, NOR HIDAYATUL; MOHD SHUKRI , NOR AZWANI; MOHD ABU BAKAR, WAN AZDIE (International Journal of Allied Health Sciences, 2020)
Introduction: Food insecurity is the state of having little or no reliable access to a sufficient quantity of affordable and nutritious food. This study was conducted to find the relationship between food insecurity with diet quality and mental health among students of International Islamic University Malaysia (IIUM) Kuantan, Pahang. Methods: This cross-sectional study involved 285 IIUM Kuantan students from six Kulliyyahs. Self-administered questionnaires adapted from Food Insecurity Experience Scale (FIES), Malaysian Healthy Eating Index (M-HEI) and Depression, Anxiety and Stress Scale (DASS-21) were used in collecting the data. Results: The outcome from the investigation of food insecurity using FIES showed an increase in food insecurity status from 54.4% in 2017 to 63.5% in this recent study. This shows that more than half of IIUM Kuantan students experience food insecurity. Results from M-HEI indicated that a majority of IIUM Kuantan students were having moderate diet quality while DASS-21 showed that a few students having very severe mental health status including depression, anxiety, and stress. However, the relationships between food insecurity and diet quality or mental health were shown to be not significant for IIUM Kuantan students. Conclusions: This study indicates that food insecurity among IIUM Kuantan students is substantial and should be monitored regularly since the prevalence shows an increasing pattern. KEYWORDS: Food Insecurity, FIES, Diet Quality, Mental Health, M-HEI, DASS-21